อัตลักษณ์ทางวัฒนธรรมกับกระบวนการกลายเป็นสินค้า : กรณีศึกษา โรงแรมปิงนครา บูติก โฮเทล แอนด์ สปาเชียงใหม่ - ธัญพัชร ศรีมารัตน์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objectives of this independent study were to 1) To study the cultural transformation in building identity that becomes commodification of Ping Nakara Boutique Hotel and Spa, Chiang Mai. 2) To study the pattern of sign or representation from the cultural transformation that becomes commodification of Ping Nakara Boutique Hotel and Spa, Chiang Mai. 3) To study the result of the cultural transformation that becomes commodification of Ping Nakara Boutique Hotel and Spa, Chiang Mai. The theoretical concept of Identity, Culture Industry, Semiology and Commodification. The study found that Lanna culture has been transformed and applied to the commodities which values to the consumers as well as adds price to the entrepreneurs. The identity of Ping Nakara Boutique Hotel and Spa, Chiang Mai springs from adapting and absorbing the identity of Lanna culture that has been existed a long time ago in the area and the contemporary art of the western countries, building the meaning and blending with the original or existed life style. Every signs existed in the hotel is the major components in building the meaning and adding the value to the hotel business. Moreover, it creates the identity as well as value to the consumers due to the historical story, nature, and culture and ultimately becomes the commodification through the selections of the entrepreneur, the architects, and the designers. However, the presentation of the hotel contains the hidden meanings according to the process of creating myths that already existed in the history, nature, and culture in the past which has been reduced, hidden, and distorted as a sign. This relates to the others signs, becoming the ordinary story. People then realized it as a common sense. Later, they has been unconsciously implanted the idea and forget about the truth. Nonetheless, the process of cultural transformation to commodification reflects the over prioritization in consuming the representations rather than the truth. Market strategy becomes the significant factor that causes the outstanding and unique. Plus, it is subject to the experience and satisfactory of the location, mood and feeling in order to attracts most consumers.